Scaling-Up the Impact of Good Practices in Rural Development : A Working Paper to Support Implementation of the World Bank’s Rural Development Strategy - World Bank (Washington, DC, 2013)
A key thrust in the implementation of the Bank's new rural development strategy is identifying and "scaling-up good practice investments and innovations in rural development." Historically, successful World Bank projects have been one-time investments without strategies for leveraging projects to a larger scale or to broader coverage to increase efficiency and developmental impact in a country or region. The Bank believes that scaling-up good practices must become an integral part of national rural development strategies to reduce rural poverty and support broad-based rural development. This working paper, written in support of the Bank's rural development strategy, is intended to contribute to the development of a framework for thinking about scaling-up. The paper begins with a review of the literature on scaling-up in rural development and other contexts to develop an understanding of basic concepts and terms. Drawing from the literature review and interviews, the authors develop a working definition of the term scaling-up and a provisional framework for analyzing experiences of scaling-up in rural development. Then, to evaluate the provisional framework, the authors apply it to a few well-documented case studies of rapid scaling-up. The final sections of the paper draw lessons from the application of the framework to the case studies and identify key areas for moving forward to support scaling-up impacts in rural development.